Dari Mahasiswa untuk Anak Negeri: Cerita di Balik Posko Ramah Anak - Ramaita Ramaita; Agusmia Intan Sari; Ficko Ari Zulian; Lusiana Suhetsyah; Rizky Rahmawati Ritonga; Suci Rahma Diati (CV. ITTC INDONESIA, 2025)
This community service activity was initiated in response to the lack of beneficial activity options for children in the Jorong Mandahiling and Piliang Laweh areas, Nagari Sumanik, during the school holidays. A